Inovasi Teknologi untuk Pariwisata Hijau: Solusi Berkelanjutan di Era Modern - Rani Andini (CV. ITTC INDONESIA, 2023)
Green tourism has become the main focus in developing the tourism sector sustainably in this modern era. Green tourism is a tourism concept that aims to minimize negative impacts on the natural and cultural environment, as well as providing balanced economic and social benefits to local communities. In an effort to overcome environmental challenges and promote environmentally friendly development, technological innovation plays an important role in facilitating the development of sustainable green tourism. This research discusses several technological innovations that can be applied in the green tourism industry to support ecological and social sustainability.